2015
DOI: 10.1080/13648470.2015.1050578
|View full text |Cite
|
Sign up to set email alerts
|

Biographical similarities between spiritual healers and their clients in Germany – a qualitative study

Abstract: Spiritual healers in contemporary Germany comprise a heterogeneous and growing group, yet little data exists about them. Therefore, one aim of this study was to learn about which biographical aspects and events were important to the process of becoming a healer and which biographical aspects drove clients to consult a healer. The study was based on semi-structured interviews combined with participant observations. All data were recorded digitally, transcribed, entered into the software program MAXQDA and analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 20 publications
(21 reference statements)
0
12
1
Order By: Relevance
“…This transformation often took many years and was often accompanied and supported by other spiritual healers and teachers. However, some of the interviewees (all with CAM or medical background) talked about becoming a healer out of sheer interest and learning to heal by attending courses in spiritual healing (for more details, see [ 38 ]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This transformation often took many years and was often accompanied and supported by other spiritual healers and teachers. However, some of the interviewees (all with CAM or medical background) talked about becoming a healer out of sheer interest and learning to heal by attending courses in spiritual healing (for more details, see [ 38 ]).…”
Section: Resultsmentioning
confidence: 99%
“…All data were discussed by the entire team according to the different disciplines and perspectives [ 36 ]. Thus, concepts from anthropological and religious studies related to our findings (e.g., concepts of embodiment and radical empathy) [ 37 , 38 ] and medically important aspects, such as symptoms or outcomes [ 39 ], could be integrated.…”
Section: Methodsmentioning
confidence: 99%
“…In biomedicine, the role of doctor and patient are treated as distinct, 9 but in healing, there is more flexibility. Clients sometimes decide to become healers, 29 and healers continue to seek healing for themselves, and to experience it while treating others. This flexibility is conducive to compassion; the healer shares in the client's healing as well as their suffering.…”
Section: Discussionmentioning
confidence: 99%
“…40 Consequently, clients were enabled to take control, in what has been described as a self-healing capacity. 6,29,31 Teut et al have previously noted self-helplike aspects in clients, such as "I totally opened myself, to my own abilities". 40(p4) Like our sample of healers, Teut et al reported that empowering people to change was a core part of the healer's role.…”
Section: Discussionmentioning
confidence: 99%
“…The research of psycho-spiritual healers and their clients focuses both on traditional ways of healing as well as on new, emerging psycho-spiritual healing practices. The basis of psycho-spiritual healing is often seen as a connection to a transcendent, nonempirical reality, which enables acquiring a new, trans- ( 39 ) formed life attitude (Stoeckigt et al, 2015). The psycho-somatic complex of some people undergoes a radical change during their life trajectories.…”
mentioning
confidence: 99%